The Influence of Breast Massage Toward Breast Milk Production on Breastfeeding of Mother - tompoliu, Destie N; Ilmiah, Widia Shofa; Maulina, Rifzul (Jurnal MID-Z (MIDWIFERI ZIGOT), 2024)
The exclusive breastfeeding program is still a global problem, including Indonesia. Data on exclusive breastfeeding coverage in Indonesia in 2021 (71.58%), 2022 (72.04%) and 2023 (73.97%). The average length of breastfeeding in Minahasa City, South Sulawesi is 9.35 months in 2019 and 10.46 months in 2021. There are various factors that cause mothers not to provide exclusive breastfeeding, both maternal and infant health factors, and other factors. Efforts are made to facilitate breast milk production, one of which is with Breast Massage. The purpose of the study was to analyze the effect of breast milk on breast milk production. Pre-experimental study design method. The population of all postpartum mothers at the Tambelang Health Center is 16 people, the sample is 16 people, the total sampling technique. The instrument used an observation sheet with a breast massage technique for 3 days carried out every day with a duration of 15-30 minutes 3 times, data analysis using the Paired T- Test. The results of the study were obtained for the age of 20-35 years (62.5%), gravida primi and multi (43.8%), and high school education (50.0%). P= 0.001 < α 0.05. Conclusion that breast massage can affect the production of breast milk for breastfeeding mothers to be smooth.